2006
DOI: 10.1094/mpmi-19-0313
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel MvaT-Like Global Regulators Control Exoproduct Formation and Biocontrol Activity in Root-Associated Pseudomonas fluorescens CHA0

Abstract: Pseudomonas fluorescens CHA0 protects various crop plants against root diseases caused by pathogenic fungi. Among a range of exoproducts excreted by strain CHA0, the antifungal compounds 2,4-diacetylphloroglucinol (DAPG) and pyoluteorin (PLT) are particularly relevant to the strain's biocontrol potential. Here, we report on the characterization of MvaT and MvaV as novel regulators of biocontrol activity in strain CHA0. We establish the two proteins as further members of an emerging family of MvaT-like regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 66 publications
1
45
0
Order By: Relevance
“…Maximum yield (q/ha) was recorded in treatment P. fluorescens @ 5g/l (223.10 q/ha) followed by T. viride @ 5g/l (213.36 q/ha) as compared to treated control (244.50 q/ha) and untreated control (103.50 q/ha). Islam and Faruq (2008), Manoranjitham et al, (1999), Bunker and Mathur (2001), Haas and De´fago (2005), Baehler et al, (2006) and Dubuis et al, (2007). Similar findings have also been reported by Karegowda et al, (2009) who found that T. viride and T. harzianum overgrew and suppressed the growth of Phytophthora capsici, Dennis and Webster, (1971) reported that Trichoderma spp.…”
Section: Resultssupporting
confidence: 67%
“…Maximum yield (q/ha) was recorded in treatment P. fluorescens @ 5g/l (223.10 q/ha) followed by T. viride @ 5g/l (213.36 q/ha) as compared to treated control (244.50 q/ha) and untreated control (103.50 q/ha). Islam and Faruq (2008), Manoranjitham et al, (1999), Bunker and Mathur (2001), Haas and De´fago (2005), Baehler et al, (2006) and Dubuis et al, (2007). Similar findings have also been reported by Karegowda et al, (2009) who found that T. viride and T. harzianum overgrew and suppressed the growth of Phytophthora capsici, Dennis and Webster, (1971) reported that Trichoderma spp.…”
Section: Resultssupporting
confidence: 67%
“…P. fluorescens strains were added as a suspension (5 ml per flask) of washed cells to give 10 7 CFU/g of soil. Seedlings were covered with nontreated soil, and the flasks were sealed and incubated as specified by Baehler et al (4).…”
Section: Methodsmentioning
confidence: 99%
“…A 1.5-kb MluI-HindIII fragment from the resulting plasmid carrying the P tac -dsred.T3_S4T fusion was then cloned into the mini-Tn7-Gm carrier plasmid, pME3280b (Zuber et al, 2003). The construct obtained, pME7160, and the Tn7 transposition helper plasmid pUX-BF13 (Bao et al, 1991) were coelectroporated (Baehler et al, 2006) into the recipient strain CHA0. The gacS mutant CHA19 (Zuber et al, 2003) was tagged with a green fluorescent protein as follows: a mini-Tn7-gfp2 cassette carrying the gfpmut3 gene controlled by a modified P tac promoter (Koch et al, 2001) was introduced into the chromosome of strain CHA19 using the transposition helper pUX-BF13, giving CHA19-g.…”
Section: Organismsmentioning
confidence: 99%